Collage Steganography - Shirali-Shahreza, M.; Shirali-Shahreza, S. (5th IEEE/ACIS International Conference on Computer and Information Science : (ICIS 2006) in conjunction with 1st IEEE/ACIS International Workshop on Component-Based Software Engineering, Software Architecture and Reuse (COMSAR 2006) : proceedings : 10-12 J, 2006)
Establishing hidden communication is an important subject of discussion that has gained increasing importance nowadays with the development of the Internet. One of the methods introduced for establishing hidden communication is steganography. Methods of steganography have been mostly applied on images while the major characteristic of these methods is the change in the structure and features of the images so as not to be identifiable by human users. However, on the other hand, many methods have been proposed for breaking and extracting information (steganalysis) for these methods. This paper presents a method for hiding information in images by changing the appearance of the picture instead of changing its features. In this method, images of a number of relevant objects are put on a scene together in a way that is not noticeable. Then, by changing the place and type of each object, information is hidden in the image because the place and type of each object indicates a special figure and, by putting the digits figures together, the information in question is hidden in the picture. Considering that in this method information has been hidden in the appearance of the picture, then by using the present methods of identification of stegano images one cannot identify the steganography images in this method or extract data from them. The proposed method has been implemented by using the Java programming language